P67Long non-coding RNAs in the infarcted heart. (15th July 2014) - Zangrando, J; Zhang, L; Vausort, M; Maskali, F; Marie, PY; Wagner, DR; Devaux, Y
Abstract: Purpose: Long non-coding RNAs (lncRNAs) constitute a novel class of non-coding RNAs. LncRNAs regulate gene expression, thus having the possibility to modulate disease progression. In this study, we investigated the expression of lncRNAs in the heart after myocardial infarction (MI). Methods: Adult male C57/BL6 mice were subjected to coronary ligation or sham operation. Cardiac gene expression was investigated using whole-genome microarrays with an in-house analytical pipeline dedicated to lncRNAs. Cardiac function was evaluated by 18F-fluorodesoxyglucose positron emission tomography (18F-FDG PET). Results: In a derivation group of 4 MI and 4 sham-operated mice sacrificed 24 hours after surgery, microarray analysis showed that MI significantly affected the cardiac transcriptome. 20 lncRNAs were up-regulated in the MI group, and 10 lncRNAs were down-regulated in the MI group (fold-change >2, false discovery rate <5%). Among these, 2 lncRNAs (called lncRNA1 and lncRNA2) showed robust up-regulation in the MI group: lncRNA1 (5-fold) and lncRNA2 (13-fold). This was confirmed using quantitative PCR, in which lncRNA1 and lncRNA2 displayed 6- and 12-fold up-regulation in the MI group, respectively (both P<0.05). Up-regulation of these 2 lncRNAs after MI was further confirmed in an independent validation group of 8 MI and 8 sham-operated mice (9-fold and 16-fold for lncRNA1 and lncRNA2, P<0.001). In a time-course analysis involving 21 additional MI mice, the expression of both lncRNAs peaked 24 hours after induction of MI and returned to basal levels after 2 days. In situ hybridization revealed an increase of lncRNA1 expression in the left ventricle of MI mice. Both lncRNAs were robustly correlated with left ventricular ejection fraction determined 24 hours after MI by 18F-FDG PET (r>0.8). Bioinformatic analyses of microarray data revealed that lncRNA1 expression displayed strong association with genes coding for proteins involved in angiogenesis, fibrosis, hypertrophy, inflammation, and extracellular matrix remodeling, all pathways involved in the development of left ventricular remodeling and heart failure post MI. Among the genes most highly correlated with lncRNA1 (r>0.80), MMP9, TNFalpha, CXCR4, and BNP were all up-regulated in the heart of MI mice. Conclusion: We show for the first time that expression of lncRNAs is regulated in the infarcted heart. This study provides the basis for future investigations of the role of lncRNAs in the diseased heart.